(untitled) (Revista de Ciências Agroveterinárias, 2023)
The existence of a wide weed diversity makes the efficient weed management necessary to avoid the weed interference and grain yield decrease. In season that El Niño is prevalent, the soil flooding is usually in paddy fields, and the cloudy time was frequent, this combination can directly decrease the weed control and rising the crop phytointoxication after the herbicide spraying. So, the objective of this research was to evaluate the paddy rice response to herbicide to shadowing and soil flooding. For that were assessed two conditions of soil saturation (with or without soil flooding), the exposing to plant rice in two light conditions, since de emergence to herbicide application (with or without shadowing) and four herbicide application: 1) check without herbicide, 2) [imazapyr + imazapic], 3) [imazapyr + imazapic] + saflufenacil e 4) [imazapyr + imazapic] + carfentrazone-ethyl. The assessed variables were phytointoxication, chlorophyll content, plant height and aboveground biomass. The herbicides caused initial phytointoxication, however there were natural recuperation of rice shoot at long of the evaluations. The paddy rice growth, of cultivar SCS121 CL, were affected by herbicide application, mainly when the tank mixture of imazapyr + imazapic plus saflufenacil or carfentrazone-ethyl. The soil flooding and the shadowing little affected the herbicide selectivity to paddy rice.